(3GdGJLGgGJ GdMOjKI ddJShjb (B:s (3eMhQ GdGOGA aj GdcjGfGJ h GdGfOeGLGJ GdGbJUGOjI , GdeONd dJMbjb GdShb GdYQHjI GdeTJQcI (B/s - (3SGdeGf, YeGO UaQs ((3GdGScfOQjI(B: s (3efTCI GdeYGQa(B, s, 2005)
(3GdJShjb GdOhdj h OhQg aj GdGShGb GdOhdjI h GdGJLGgGJ GdMOjKI ddJShjb , GdJShjb GdGdcJQhfj h GdJLGQI GdGdcJQhfjI cCOGI JShjbjI eYGUQI eY GdJWQb Gdi eaghe GdbOQI GdJfGaSjI h GdejRI GdfSHjI h eDTQGJ GdbjGS h cPdc GdbOQI GdJfGaSjI ddefXeGJ cCOGI JShjbjI h GdeJZjQGJ GdYGdejI h GdJcJdGJ GdGbdjejI h CNjQG GdJWQb Gdi JCKjQ GdGJLGgGJ GdMOjKI ddJShjb h GdJcJdGJ h GdGfOeGLGJ Ydi GdShb GdYQHjI GdeTJQcI(B.s
Keywords: (3GdJShjbs; (3GdJcGed GdEbJUGOjs; (3GdShb GdYQHjI GdeTJQcIs